2015
DOI: 10.4168/aair.2015.7.6.590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Retinoic Acid in a Mouse Model of Allergic Rhinitis

Abstract: PurposeAll-trans retinoic acid (ATRA) modulates immune responses by affecting T cells. Several studies have revealed that allergic inflammation of the lower airways is negatively associated with the vitamin A concentration. However, the role of ATRA in allergic inflammation of the upper airways is unclear. We investigated the effects of ATRA in an allergic rhinitis mouse model.MethodsBALB/c mice except control groups (CON group) were sensitized with and challenged intra-nasally with Dermatophagoides farina (AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
3
9
2
Order By: Relevance
“…In our study, OVA specific IgE, OVA specific IgG1, and OVA specific IgG2a were significantly increased with intraperitoneal OVA sensitization which did not decrease after intranasal treatment with steroid or PPC. This might be different from previous studies which reported intranasal treatment with steroid or other therapeutic materials lowered blood levels of OVA specific IgE [ 13 , 23 ]. Interestingly, as mentioned above, serum levels of IL-4 were lower in the PPC and CIC groups in comparison with AR group.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, OVA specific IgE, OVA specific IgG1, and OVA specific IgG2a were significantly increased with intraperitoneal OVA sensitization which did not decrease after intranasal treatment with steroid or PPC. This might be different from previous studies which reported intranasal treatment with steroid or other therapeutic materials lowered blood levels of OVA specific IgE [ 13 , 23 ]. Interestingly, as mentioned above, serum levels of IL-4 were lower in the PPC and CIC groups in comparison with AR group.…”
Section: Discussioncontrasting
confidence: 99%
“…This might be different from previous studies which reported intranasal treatment with steroid or other therapeutic materials lowered blood levels of OVA specific IgE [13,23]. Interestingly, as mentioned above, serum levels of IL-4 were lower in the PPC and CIC groups in comparison with AR group.…”
Section: Discussioncontrasting
confidence: 81%
“…The active metabolite of vitamin A, retinoic acid (R.A.), is involved in transcriptional control of ciliogenesis (36,41,42). R.A. has anti-allergic effects in mice (43,44) and in vitro cell models. Growing primary airway epithelial cells in the absence of R.A. induces a squamous phenotype (45).…”
Section: Impaired Ciliogenesis Resulting From Cigarette Smoke Condensmentioning
confidence: 99%